The Legal Maxim: “Imitation of What Is Deficient Is Prohibited in Islamic Law” — A Jurisprudential Study on Triviality Phenomenon - Waqas Farhan Hamoud (Islamic Sciences Journal, 2025)
ABSTRACT This study explores the Islamic legal maxim: “Imitation of what is deficient is prohibited in Sharia” as a foundational principle in guiding behavior and regulating manifestations of moral deviation. In light of the growing wave of frivolity and the rise of false role models across media and social platforms, the research highlights the significance of this maxim in establishing clear criteria for distinguishing between upright conduct and ethical decline, based on the standards of Islamic law. The study examines how "deficiency" is defined jurisprudentially and identifies who qualifies as “frivolous” from a Sharia-based perspective. It also investigates the root causes of the spread of superficiality in modern society and offers educational and legal proposals to address this phenomenon, emphasizing the vital role of educators, scholars, and social awareness leaders in shaping a generation that upholds its values and takes pride in its identity.